JEZIK: LINGVISTIČKA, KULTURNA I/ILI DRUŠTVENA KATEGORIJA (Филологические заметки, 2019)
Language is used for human communication, which is its basic and broadest purpose. Language divisions relevant to different varieties, such as geographical and social dialects, standard types and their varieties, all kinds of subtype language idioms, always blend with the social varieties. Thus, language is a social category, and is accordingly the condition, but also the consequence of social changes with far reaching consequences for the culture of the community that uses it. The sociolinguistic research represents the interdisciplinary complex close to the recent cultural studies which deal with the Other. When differences are emphasized between the individual speaker and the collective, that results with the situation of language discontinuity, a factor of great instability which contributes to fitting/not fitting in the coherent cultural stream. The relation between language and culture is not only affirmative as in ideal contemporary big and powerful multicultural and multilingual socities, but it can also be antagonistic. For instance, the relations beetwen languages of colonizers and languages of colonized societies, or those inside a society, in the process of standardization, almost always eliminate the elements of the minor culture and its language.